Evaluación de cuatro tipos de poda de mantenimiento en el cultivo de cacao (Theobroma cacao) CCN-51 en la zona de Zapotal, Provincia de Los Ríos. - Engracia Manobanda, Jorge Haron (2018)
The cultivation of cacao (Theobroma cacao) has a large presence in a high and growing number of hectares of agricultural use, distributed throughout almost the entire Ecuadorian territory. The agronomic management of this crop consists of different cultural tasks, one of the main ones is maintenance pruning. In many farms the maintenance pruning is carried out in a wrong way which becomes a problem, since tree does not maintain the ideal structure, driving to a low production, for this reason alternatives of maintenance pruning that annul the practice of pruning were raised. drastic, such as carrying out several light prunings in the year that have minimal negative effects and potentiate crop yield; based on this, the present investigation was proposed "Evaluation of four types of maintenance pruning in the cocoa (Theobroma cacao) ccn-51 crop in the zone of Zapotal, province of Los Ríos" that pursued the objectives of comparing the effects of different types of maintenance pruning against a pruning control treatment characteristic of the area, determine the incidence of diseases in cocoa CCN-51 in relation to the types of maintenance pruning and establish the frequency of maintenance pruning of greater positive effect in health and yield of the CCN-51 cocoa crop. The research was carried out in an established CCN-51 clonal cocoa plantation of 4 years old, located in the Zapotal Parish (via Las Naves) of the Ventanas canton, Province of Los Ríos, at coordinates 1º 21 '30.5 "of latitude South and 79º 23 '44.4 "and longitude West, with an altitude of 19 meters above sea level. We used the design of complete blocks at random in four repetitions, evaluating 4 types of maintenance pruning plus a characteristic treatment of the sector and an unpruned control. After the interpretation and analysis of the results, the following conclusions were obtained; the application of light pruning generated positive effects to a great extent, with low percentages of incidence of diseases and a treatment with increased yield of 1216.8 kg/ha above the farmer treatment. The light prunings do not alter the physiology of the cacao plant compared to drastic pruning, evidencing in the obtained yields. Key words: Maintenance pruning, light pruning, drastic pruning, pruning, CCN-51, yield.